2016
DOI: 10.1007/s12034-016-1317-5
|View full text |Cite
|
Sign up to set email alerts
|

Loss of outer membrane integrity in Gram-negative bacteria by silver nanoparticles loaded with Camellia sinensis leaf phytochemicals: plausible mechanism of bacterial cell disintegration

Abstract: New generation antimicrobial and smart drugs are the needs of the present era in fighting microbial infection and various chronic diseases. Nowadays nanoparticles (NPs) are widely applied in biomedical fields by virtue of their surface modification, which enhances both target selectivity and function. This study is a continuation of our earlier study that demonstrated antimicrobial property of NPs against both Gram-positive and Gramnegative organisms (Goswami et al, 2015). Silver NPs were synthesized using tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 24 publications
3
25
1
Order By: Relevance
“…Further studies revealed that cytoplasmic leakage and lipid peroxidation are the possible mechanisms of action of aPDT on the test bacterial species. It can also be concluded that the major target of ROS was the cell membrane that resulted in protein leakage and lipid peroxidation, as previously suggested by other authors (Misba et al 2016;Singh et al 2016;Misba et al 2017).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Further studies revealed that cytoplasmic leakage and lipid peroxidation are the possible mechanisms of action of aPDT on the test bacterial species. It can also be concluded that the major target of ROS was the cell membrane that resulted in protein leakage and lipid peroxidation, as previously suggested by other authors (Misba et al 2016;Singh et al 2016;Misba et al 2017).…”
Section: Discussionsupporting
confidence: 75%
“…CTAB (N,cetyl-N,N,N-trimethylammonium bromide) was used as a positive control in order to release the complete protein content inside the cells. The assay was performed similar to the protocol described by Singh et al (2016). Test cultures were treated with MSN, TB, and TB MSN at the same concentrations used for antimicrobial photodynamic inactivation.…”
Section: Cytoplasmic Protein Leakagementioning
confidence: 99%
“…Some studies revealed that extracts from Cabernet Sauvignon grape pomace exhibited higher antimicrobial activities compared to Syrah and Merlot pomaces, as a result of the total phenolics contents differences (Oliveira et al, 2013;Sanhueza et al, 2014). Antimicrobial activity against S. aureus and Listeria monocytogenes of different grape pomace varieties extracts was also reported by Xu et al (2016), whereas for Salmonella typhimurium and E. coli growth no effects were obtained, probably due to the cell structure of Gram-negative bacteria, which have two-layer cell membrane and high outer membrane hydrophilicity, leading to great resistance on grape pomace extracts (Singh, Mallick, Banerjee, & Kumar, 2016;Xu et al, 2016). On contrary, other study reported growth inhibition of grape pomace on both Gramnegative and Gram-positive bacteria, depending on the extract concentration, better results being obtained at higher extract concentrations (Faisal, Mosammad, & Heri, 2015).…”
Section: Antimicrobial Propertiesmentioning
confidence: 87%
“…Due to the mechanism of action of NPs against other Gram-negative bacteria, specifically targeting the membrane integrity [37], we evaluated changes in OMPs expression under the different NPs treatments (Figs 6 and 7). OMPs fractionation allowed us to identify the most abundant pore-forming proteins (porins) in V. cholerae: OmpT and OmpU, and the OMPs: OmpC, OmpA and OmpW.…”
Section: Discussionmentioning
confidence: 99%